Müller glia–microglia cross talk reprograms the Müller glia transcriptome for cell division–related processes during retina regeneration - Soumitra Mitra; Sulochana Devi; Mi-Sun Lee; Aresh Sahu; Jonathan Jui; Emil Kriukov; Petr Baranov; Daniel Goldman (Proceedings of the National Academy of Sciences, 2026)
In the zebrafish retina, Müller glia (MG) respond to retinal injury by dividing and producing a multipotent progenitor for retinal repair. This cell division is regulated by microglia; however, the underlying mechanism remains unknown. Here, we report that MG-derived Il34 attracts microglia to sites of retinal injury where they stimulate MG proliferation via the release of cytokines, like M17, Spp1, Tnfa, and Tnfb. Remarkably, RNA sequencing analysis of MG’s regeneration-associated transcriptome with and without microglia depletion suggests microglia stimulate MG proliferation by preferentially enhancing the expression of regeneration-associated genes involved in cell division–related processes. In contrast, genetic ablation of essentially all microglia from early development appears to reprogram MG, so they exhibit enhanced injury-dependent proliferation, but their survival is compromised. Our studies illustrate the profound effects MG-microglia cross talk can have on MG transcriptional programs related to cell division processes.